The role of the arts in Finnish education as informed by teacher narratives - Hand, Lauren Maciasz (2019)
This study aims to explore the Finnish Education system through a novel focus of the role of the arts in compulsory education. This study aims to explore the role of the arts in Finnish education through three domains: teachers’ view on the arts and its role in education, perceived effect of the arts on student development, and characteristics of the Finnish education system that influence the degree to which teachers integrate the arts. This qualitative study was conducted in Jyväskylä, Finland with six primary school, general education teachers. Data was collected by means of interviews and analyzed according to narrative analysis. Evident in the narratives of teachers is an understanding of art that expound on its individualistic and inclusive qualities. Also, present is the strong opinion that the arts should be taught in discipline specific and integrated forms. Additionally, teacher perceptions of student development from arts-based activities such as improved self-esteem and increased concentration are shared. Reasons why teachers are creative and use the arts in their teaching point to the high degree of autonomy they possess in the Finnish education system. Supportive and trusting school leadership and close collaboration with colleagues are aspects that are perceived to contribute the most to the teachers’ sense of autonomy. A key finding from this study recognizes that the Finnish Education system has been conducive to learning in and through the arts. It is hoped that education systems around the world can glean understanding for best practices from aspects highlighted in this work.